Nigerian Construction Professional's Education And Deficiencies In The Area Of Project Management - Ameh , Oko John; Odusami , Koleola Tunwase (Penerbit Universiti Sains Malaysia, 2014)
This study examined the extent to which Nigerian construction professional groups are equipped with relevant degree-specific knowledge in project management practice. A survey was employed, in which 60 construction project managers based in Lagos, Nigeria were selected using the snowball sampling technique. Data were analysed using descriptive statistics. The findings indicate that construction project managers are proficient in construction technology, project planning and control and contract administration, while they are deficient in information technology, marketing, accounting and finance and human and industrial relations. The quantity surveyors' group and the builders' group are the most equipped, whereas the civil engineers' group is the least equipped in terms of background education to practise project management. The study can be used as a guide by clients when engaging built environment professionals to aid in construction project management. The current study provides insight into proficiency and highlights the deficiencies of the various built environment professionals in the management of construction projects.